Odpowiedź :
a) L = 2πr , r
L = 2πr /:2π
r = L/2π
b) P = 1/2ah , h
P = 1/2ah /*2
2P = ah /:a
h = 2P/a
c) h= a pierwiastek z 3 przez 2 , a
h = (a√3)/2 /*2
2h = (a√3) /:√3
a = 2h/√3 = (2√3 h)/3
d) P=cd/2 , d
P = cd/2 /*2
2P = cd /:c
d = 2P/c
e) V = 1/3ab * H , h
V = 1/3ab * H /*3
3V = ab * H /:ab
H = 3V/ab
f) P = πr² ,r
P = πr² /:π
r² = P/π
r = √P/√π = (√P*√π)/π
g) v = πR² * H , R
v = πR² * H /:πH
R² = v/πH
R = √v/√π√H = (√v*√π*√H)/πH
h) P= (a+b)h przez 2 .a
P = [(a+b)h]/2 /*2
2P = (a+b)h /:h
a+b = 2P/h
a = 2P/h - b
i) P=πr(r+l) , l
P=πr(r+l) /:πr
r+l = P/πr
l = P/(πr) - r
L = 2πr /:2π
r = L/2π
b) P = 1/2ah , h
P = 1/2ah /*2
2P = ah /:a
h = 2P/a
c) h= a pierwiastek z 3 przez 2 , a
h = (a√3)/2 /*2
2h = (a√3) /:√3
a = 2h/√3 = (2√3 h)/3
d) P=cd/2 , d
P = cd/2 /*2
2P = cd /:c
d = 2P/c
e) V = 1/3ab * H , h
V = 1/3ab * H /*3
3V = ab * H /:ab
H = 3V/ab
f) P = πr² ,r
P = πr² /:π
r² = P/π
r = √P/√π = (√P*√π)/π
g) v = πR² * H , R
v = πR² * H /:πH
R² = v/πH
R = √v/√π√H = (√v*√π*√H)/πH
h) P= (a+b)h przez 2 .a
P = [(a+b)h]/2 /*2
2P = (a+b)h /:h
a+b = 2P/h
a = 2P/h - b
i) P=πr(r+l) , l
P=πr(r+l) /:πr
r+l = P/πr
l = P/(πr) - r
a). L=2πr , r
r=L:(2π)
b). P=1/2ah , h
2P/a=h
c). h= a pierwiastek z 3 przez 2 , a
2h/√3=a
d). P=cd/2 , d
2P/c=d
e). V=1/3ab * H , h
H=3V/ab
f). P=πr² ,r
r²=P/π
r=√(P/π)
g) v=πR² * H , R
R²=V/πH
R=√(V/πH)
h). P= (a+b)h przez 2 .a
2P=ah+bh
2P-bh=ah
(2P-bh)/h=a
i) P=πr(r+l) , l
P=πr²+πrl
P-πr²=πrl
(P-πr²)/πr=l
r=L:(2π)
b). P=1/2ah , h
2P/a=h
c). h= a pierwiastek z 3 przez 2 , a
2h/√3=a
d). P=cd/2 , d
2P/c=d
e). V=1/3ab * H , h
H=3V/ab
f). P=πr² ,r
r²=P/π
r=√(P/π)
g) v=πR² * H , R
R²=V/πH
R=√(V/πH)
h). P= (a+b)h przez 2 .a
2P=ah+bh
2P-bh=ah
(2P-bh)/h=a
i) P=πr(r+l) , l
P=πr²+πrl
P-πr²=πrl
(P-πr²)/πr=l